Commercializing Africa's Roads : Transforming the Role of the Public Sector - Heggie, Ian G. (World Bank, Washington, DC, 2012)
Road transport is the dominant mode of transport in sub-Saharan Africa, carrying close to 90 percent of the region's passenger and freight transport, and providing the only access to rural communities where over 70 percent of Africans live. Despite their importance, most of the region's nearly 2 million km of roads are poorly managed and badly maintained. By 1990, nearly a third of the $150 billion invested in roads had been eroded through lack of maintenance. To restore only those roads that are economically justified and prevent further deteriorations will require annual expenditures of at least $1.5 billion over the next ten years, or more than double the requirements of regular maintenance. To find sustainable solutions to these problems, the United Nations Economic Commission for Africa (UNECA) and the World Bank launched the Road Maintenance Initiative (RMI) as part of the sub-Saharan Africa Transport Policy Program (SSATP). With support from a number of bilateral donors, the Initiative has spent the last six years working with African countries to identify the causes of poor road maintenance policies and to develop an agency for reforming them. The key concept to emerge from the debate on how to strengthen financing and management of roads is commercialiation: bring roads into the marketplace and put them on a fee for service basis. However, since roads are and will largely remain a public monopoly, commercialization requires complementary reforms.